Analisis Pengaruh Customer Satisfaction Terhadap Customer Loyalty Dengan Customer Retention Sebagai Variabel Intervening - Ika Marsita Handayani; Adhitya Yoga Prasetya (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze the influence of customer satisfaction on customer loyalty which is mediated by customer retention as an intervining variable in the case study of Bank Syariah x in West Semarang. The dependent variable analyzed in this research is customer loyalty. The independent variable analyzed in this research is customer satisfaction. The sample used in this research was Bank Syariah X customers in West Semarang consisting of 100 respondents. Sample collection was carried out using the accidental sampling method, which is an accidental sampling method by taking cases or respondents who happened to be present or available in the area of the research. This research uses the Structural Equation Modeling (SEM) analysis method. The results of this research show that customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer retention. Customer retention has a positive and significant effect on customer loyalty. Another result of this research is that customer satisfaction has a positive and significant effect on customer loyalty through customer retention as an intervining variable.